2009
DOI: 10.1007/s10151-009-0546-7
|View full text |Cite
|
Sign up to set email alerts
|

External validation of Cleveland Clinic Foundation colorectal cancer model in a University Clinic in terms of predicting operative mortality

Abstract: BackgroundThe aim of this report is to analyse our results and to underline our criteria for day surgery practice.Patients and methodsOur patients are selected according to ASA criteria. Occasionally, the patients with some risk factors are selected but only when their concomitant diseases are well controlled.ResultsWe have treated 673 patients with the third and early fourth degree haemorrhoids. We have had patients with several minor problems causing no influence on the success of the procedure. Good haemost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…Parameters that were included in the risk score were age, ASA, TNM stage, mode of presentation, haematocrit level and cancer resection. External validation demonstrated good discriminating performance but poor calibration .…”
Section: Discussionmentioning
confidence: 99%
“…Parameters that were included in the risk score were age, ASA, TNM stage, mode of presentation, haematocrit level and cancer resection. External validation demonstrated good discriminating performance but poor calibration .…”
Section: Discussionmentioning
confidence: 99%
“…(911) Upon external validation, however, both CR-POSSUM and ACPGBI underestimated mortality, and showed poor discrimination (16). Furthermore, although the CCF-CCM model exhibited good discriminative performance, it lacked calibration when assessed in CRC patients from a single university clinic (37). Our model showed fair calibration using the Hosmer-Lemeshow goodness-of-fit test.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen prognostic models for short‐term mortality after colorectal surgery were identified in English‐language journals, the largest of which included 975 825 patients ( Table S1 , supporting information). Seven of the models were developed for patients with colorectal cancer, and the largest of these included 7374 patients.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that the nine published models identified that reported discriminatory ability within their own sample are overoptimistic in their estimates of discrimination. Three of these nine models were validated in a different health system and their discriminatory ability in these external data sets was often substantially lower than in the original data sets (0·90 reduced to between 0·69 and 0·78; 0·78 reduced to between 0·70 and 0·73; 0·8 maintained at 0·81). Four of the other six models are likely to suffer from a large amount of overfitting as the models were developed on fewer than 300 deaths.…”
Section: Discussionmentioning
confidence: 99%